Revision of the genus Tmesiphorus LeConte, 1849 (Coleoptera: Staphylinidae: Pselaphinae) from Japan - Inoue, Shota; Maruyama, Munetoshi; Nomura, Shûhei (Zootaxa, 2019)
The Japanese species of the genus Tmesiphorus are revised: three known species are redescribed and two new species are described. They are: Tmesiphorus costatus Weise, T. crassicornis Sharp, T. princeps Sharp, T. kinomurai sp. nov., and T. okinawensis sp. nov. A key to species is provided. Four species, T. crassicornis, T. princeps, T. kinomurai sp. nov. and T. okinawensis sp. nov., are recognized as obligate myrmecophiles.